Duration of Posttraumatic Amnesia Predicts Neuropsychological and Global Outcome in Complicated Mild Traumatic Brain Injury. Issue 6 (November 2016) - Hart, Tessa; Novack, Thomas A.; Temkin, Nancy; Barber, Jason; Dikmen, Sureyya S.; Diaz-Arrastia, Ramon; Ricker, Joseph; Hesdorffer, Dale C.; Jallo, Jack; Hsu, Nancy H.; Zafonte, Ross
Abstract : Objectives: Examine the effects of posttraumatic amnesia (PTA) duration on neuropsychological and global recovery from 1 to 6 months after complicated mild traumatic brain injury (cmTBI). Participants: A total of 330 persons with cmTBI defined as Glasgow Coma Scale score of 13 to 15 in emergency department, with well-defined abnormalities on neuroimaging. Methods: Enrollment within 24 hours of injury with follow-up at 1, 3, and 6 months. Measures: Glasgow Outcome Scale-Extended, California Verbal Learning Test II, and Controlled Oral Word Association Test. Duration of PTA was retrospectively measured with structured interview at 30 days postinjury. Results: Despite all having a Glasgow Coma Scale Score of 13 to 15, a quarter of the sample had a PTA duration of greater than 7 days; half had PTA duration of 1 of 7 days. Both cognitive performance and Extended Glasgow Outcome Scale outcomes were strongly associated with time since injury and PTA duration, with those with PTA duration of greater than 1 week showing residual moderate disability at 6-month assessment. Conclusions: Findings reinforce importance of careful measurement of duration of PTA to refine outcome prediction and allocation of resources to those with cmTBI. Future research would benefit from standardization in computed tomographic criteria and use of severity indices beyond Glasgow Coma Scale to characterize cmTBI.